Asuhan Keperawatan pada An. D dengan Infeksi Saluran Pernapasan Akut (ISPA) dengan Masalah Bersihan Jalan Napas Tidak Efektif dengan Penerapan Terapi Uap Minyak Kayu Putih di Rumah Sakit Harapan Bunda - Novrizal, Yogi; Febrina, Trisya Yona (PPNI UNIMMAN, 2025)
Acute respiratory tract infections (ARTIs) indicate a higher prevalence among children compared to other infections, contributing to over 870,000 deaths of children under five years of age each year, or approximately 2,320 children every day. Eucalyptus oil contains chemical compounds such as eucalyptol, cineole, linalool, and terpineol, which produce a warming sensation when applied to the skin. Inhaling eucalyptus oil can relieve respiratory problems because the vapor acts as a decongestant, helping reduce nasal congestion, ease breathing, thin mucus for easier expulsion, and maintain moisture in the respiratory mucosa.The purpose of this study was to analyze nursing care for children with acute respiratory tract infections (ARTIs) experiencing ineffective airway clearance using the intervention of warm water vapor and eucalyptus oil inhalation. The method used was a case study, with data collected through interviews with the patient’s family, observation, physical examination, and nursing documentation.The coloring therapy intervention was given once daily for three consecutive days during the implementation phase. After the administration of warm water vapor and eucalyptus oil therapy to patient An.D, who had an acute respiratory tract infection with ineffective airway clearance, there was an observable improvement in cough intensity and mucus expulsion. The patient’s respiratory rate decreased from 42 breaths per minute to 30 breaths per minute, and oxygen saturation (SpO₂) returned to normal.It can therefore be concluded that warm water vapor and eucalyptus oil therapy has a positive effect on children with acute respiratory tract infections (ARTIs) who experience ineffective airway clearance.